The use of reduced and ball games for training of the foundation pass in a beginning football team - Rodigues, Marcelo Francisco (2020)
Introduction: Currently, field football teams are looking for ways of training to improve the game techniques to improve the use of these actions. An important foundation for this team to achieve important results is the pass, because through this foundation that a team can move the ball around the field. Objective: To verify if training based on ball games and reduced games can influence the improvement of the pass foundation in field football. Methods: Twenty-three male individuals aged 11.74 Â± 1.63 years old participated in the study, who undertook a training proposal in 16 sessions based on the global / functional method as a teaching method with emphasis on games with balls in the feet. Two games were filmed (open to the public), one before and one after the practical interventions (GAME 1 and GAME2) and a simple scout was obtained to obtain the data from the game 1 and game 2 passes. A descriptive analysis of the data was performed, observational analysis and a Student's t test to compare the means of the collections performed. Conclusion: It was observed after the training sessions period that it was possible to notice the increase in the number of forward passes in the midfield and attacking sectors and the decrease in the defensive sector.